Investigation on EM radiations from interconnects in integrated circuits - Lounas Belhimer; Arezki Benfdila; Ahcene Lakhlef (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
Characterization and estimation of interconnections behavior in integrated circuits design before the implementation phase is of paramount importance. This behavior seen as microstrip antennas gets complex as the internal signal (square or sine waves) frequencies increase. Thus, they become the preferred path for the propagation of electromagnetic disturbances. In this work we have worked out the numerical modeling of the electromagnetic interactions characterizing the electromagnetic compatibility in the microstrip transmission lines. The effect of these electromagnetic interactions in different structures topologies are studied through the analysis of the influence of the supply signals frequency and structures. The spacing between transmission line tracks and the number of tracks superposition is modeled. The evolution and variation of the scheme parameters in the frequency domain are determined. The transmission lines are considered parallel of equal spacing and superposed tracks of equal spacing and thickness. The capacitance and inductance matrices are computed and discussed. The results are found to comply with current research outcomes.